Reliability and Validity of the Czech Version of the Pittsburgh Sleep Quality Index in Patients with Sleep Disorders and Healthy Controls - Manková, Denisa; Dudysová, Daniela; Novák, Jan; Fárková, Eva; Janků, Karolina; Kliková, Monika; Bušková, Jitka; Bartoš, Aleš; Šonka, Karel; Kopřivová, Jana (BioMed research international, 2021)
Objectives: Psychometric properties of the Czech version of the Pittsburgh Sleep Quality Index (PSQI-CZ) have been evaluated only in patients with chronic insomnia, and thus, it is unclear whether PSQI-CZ is suitable for use in other clinical and nonclinical populations. This study was aimed at examining the validity and reliability of the PSQI-CZ and at assessing whether the unidimensional or multidimensional scoring of the instrument would be recommended. Methods: A total of 524 adult subjects from the Czech population participated in the study. The internal consistency of PSQI was evaluated using Cronbach's alpha. The known-group validity was tested using the Kruskal-Wallis H test to verify the difference between patients with sleep disorders and healthy control sample. For testing the structural validity, a cross-validation approach was used with both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). For EFA, the maximum likelihood method with direct oblimin rotation and parallel analysis was used. Results: The internal consistency of PSQI-CZ items was moderate (α = 0.75). Receiver operating characteristic (ROC) curve analysis showed high specificity (0.79) and moderate sensitivity (0.64) using an optimal cut-off score of 10. The EFA revealed a 3-factor structure with factors labelled as "sleep duration and efficiency," "sleep disturbances and quality," and "sleep latency." The CFA showed that the emerged 3-factor model had a partly acceptable fit, which was better than other previously supported models. Conclusions: A high cut-off score of 10 is recommended to define poor sleep quality. Given the inconsistency of structural analyses, alternative scoring was not recommended. However, the individual components in addition to a total score should be interpreted when assessing sleep quality. We recommend editing and verifying the PSQI-CZ translation.
Keywords: dospělí; Female; Psychometrics; psychometrie; Adult; ženské pohlaví; Reproducibility of Results; Sleep Wake Disorders; lidé; studie případů a kontrol; faktorová analýza statistická; poruchy spánku a bdění; ROC křivka; reprodukovatelnost výsledků; Male; Case-Control Studies; Czech Republic; překládání; Česká republika; Translating; mužské pohlaví; Factor Analysis, Statistical; ROC Curve; Humans